Revolusi Industri 4.0: Tantangan dan Peluang Manajemen Sumber Daya Manusia Untuk Meningkatkan Produktivitas Grand Hotel Jambi - Hendriyaldi Hendriyaldi (J-MAS (Jurnal Manajemen dan Sains), 2019)
In the era of the digital revolution, human resources became an important factor in the success of the company. Companies are required to be able to turn challenges into opportunities that can be more productive, innovative, and adaptive in each generation. The purpose of this study is to determine the challenges and opportunities for human resource management at Grand Hotel Jambi and determine strategies in developing human resources to increase productivity at the Grand Hotel Jambi. This research uses descriptive qualitative research. Data collection techniques are used as follows observation, interview, documentation, and literature study. The validity of the data uses triangulation of examination techniques using sources. The results of this study are the challenges faced by the Grand Hotel Jambi human resource management in the industrial revolution 4.0, the difficulty in getting education staff majoring in hospitality, the low ability of technology and foreign languages. Technological advances provide opportunities for Grand Hotel Jambi to increase productivity such as increasing hotel bookings due to providing information and promotions to customers more quickly. Then Grand Hotel Jambi continues to make changes in policy and program strategies for human resource development such as applying 3 aspects of assessment namely work discipline employees, attitude in work and employee skills. In addition, organizing training programs to develop the skills, knowledge and attitudes of employees. The training program must analyze 3 processes, namely company analysis, employee qualification analysis, employee performance analysis